Lessons for Leaders on the Preparation of Literacy Educators. (June 2019) - Bomer, Randy; Maloch, Beth
In this commentary, drawing from reviews of research on literacy teacher preparation, the authors discuss points of leverage in preparation of literacy educators for deans and associate deans. Categories that leaders might attend to include: mediated field experiences, faculty development, and external reputation.